FIRE DETECTION BASED ON IOT THROUGH FIBER TO THE HOME (FTTH) - Sri Danaryani; Verawati Agustina; Fuanisa Bonita Herlina Syamsudin (Jurnal Poli-Teknologi, 2018)
ABSTRACTFires can occur anytime and anywhere and fires are generally known after the fire has begun to grow. Therefore, it is necessary to detect fires that can quickly detect the presence of a fire and prevent fires from getting bigger. This research has made a fire detection equipment where the detection results can be received remotely by utilizing the internet network through FTTH. The transmitter equipment consists of a fire detector using the MQ-2 gas sensor, LM35DZ temperature sensor, processing data using Arduino that is connected to an Ethernet shield and FTTH. The receiver consists of an Ethernet shield, Arduino, and an alarm and LED circuit. Changes in smoke temperature and thickness were detected by Arduino. When the LM35DZ temperature sensor detects temperature changes greater than or equal to 350C and the gas sensor MQ-2 detects smoke thickness greater than or equal to 150ppm, the Arduino microcontroller will provide logic 1 and will activate the buzzer and led. Conversely, if the temperature and smoke thickness are less than the conditions above, Arduino sends logic 0. Arduino uno is connected to the Ethernet shield so that data from Arduino can be sent via the internet using FTTH network. In the receiver, if the data received by logic 1 will activate the buzzer and led which indicates the temperature above 35 degrees and smoke thickness above 150 ppm. Transmitter devices and receivers can be interconnected through FTTH networks with IP addresses that are one network, where the IP transmitter device is 172.31.16.27 and the IP device is 172.31.16.29. The QOS test results for FTTH network are good with packet loss 0 and very small delay which is <150 ms and throughput above 1Mbps.Key : Arduino, buzzer, LED, Ethershield, Fiber To The Home,IoT